Morphological, Biochemical, and Climatological Analysis of Three Moroccan Henna Verities - Soukaina El Massoudi; Meryem Benidir; Rachida Chabir; Meryem Benjelloun; Lahsen El Ghadraoui; Faouzi Errachidi (The Scientific World Journal)
In this study, we aimed to evaluate planted Henna in three sites in Morocco, namely, Alnif, Tafraoute Sidi Ali, and Tazzarine. Morphometric study shows that Tafraoute Sidi Ali Henna variety has highest geometric and weight parameters (length of 27.48 mm, width of 10.92 mm, specific mass of 25.1 mg/leaf, leaf area of 51, 53 mm2, and rib’s number of 9.41) when compared to Alnif and Tazzarine varieties. On the other hand, biochemical analysis shows that Tazzarine Henna variety, in the first rank, is characterized by high levels of total sugars (11.27 g/100 g), reducing sugars (5.59 g/100 g), proteins (4.4 g/100g), lipids (3.05 g/100g), phenolic compounds (31.9 g/100 g), flavonoids (5.68 g/100 g), and tannins (5.5 g/100 g). Chromatographic study shows that Tazzarine Henna variety is rich in monocyclic and polycyclic phenolic compounds. Climatic conditions analysis shows that the morphometric and biochemical diversity is related to hydrous and thermal profiles of studied sites. As a conclusion of this work, we can recommend the use of morphometric analysis and phytochemical and chromatographic analysis to determine the quality of Henna in Morocco and elsewhere.